Public television and media literacy: the role of TV ombudsman programmes in Portugal and Brazil - Pereira, Sara (2016)
Is Media Literacy a dimension of the Public Service of the Media? Does public service television, in Portugal and in Brazil, contemplate Media Education in their policies and grids? Taking these questions as a departure and debating point, we have used sixteen editions of the ombudsman programmes of the public broadcasting companies of Brazil (Empresa Brasil de Comunicação – EBC) and Portugal (Rádio e Televisão de Portugal – RTP) as analysis corpus. In order to examine O Público na TV (The Public on TV) from EBC and A Voz do Cidadão (The Citizen’s Voice) from RTP, we have used a set of analysis categories which will allow, among other aspects, to understand the contribution of these programmes to the promotion of Media Literacy of the societies where they are broadcast and of the public they will reach. Generally speaking, the results show that, by developing a role of mediation with the public/audiences, the Ombudsman plays an important role as a Literacy Agent for the Media towards those audiences, even though that role could be reinforced and could express, in a more direct and clear form, the objective of Media Literacy.